La educación primaria en Europa - García Garrido, José Luis (Revista Española de Pedagogía, 2018)
This article, rather than a simple description of features and facts, is aimed at a revision of the main problems which affect today to the primary level of formal education in Europe. However, for a right understanding of these problems, some reference is made to the historical evolution of "primary education" as a concept and as a set of educational institutions, and also to the different forms adopted by European education systems in terms of institutional and administrative structures. As to the problems, they have been selected having into account the priorites actually given nowadays by the countries, and they refer namely to the quality of primary education, relationships between public and private agencies, decentralization, school integration of ethnic minorities and handicapped children, curricula, etc. The quality of teaching staff is greatly stressed as the main problem.
Keywords: educación primaria